Consumption of legal and illegal drugs in adolescents in times of COVID-19: Consumption of legal and legal drugs in adolescents in times of COVID-19 - Noh Moo, Pedro Moises; Ahumada Cortéz, Jesica Guadalupe; Miguel Angel, Miguel Angel; Valdez Montero, Carolina; Castillo Arcos, Lubia de Carmen; Lopez Cisneros, Manuel Antonio (Horizonte Sanitario, 2022)
Objective: To know the consumption of tobacco, marijuana and cocaine in Mexican adolescents in times of COVID-19. Materials and methods: Quantitative, descriptive and cross-sectional study carried out with 265 Mexican adolescents between 12 and 19 years of age, chosen through a non-probabilistic sampling. The information was collected using the SurveyMonkey digital platform, the data was processed in the SPSS 23.0 statistical program. Descriptive statistics were used to obtain frequencies, proportions, measures of central tendency and variability. Results: The average age was 17.8 years, the start of alcohol consumption was at 16.7 years, tobacco at 16.8 years, marijuana at 17 years and cocaine at 17.3 years. The average number of alcoholic beverages consumed on a typical day was 3.3, the average number of cigarettes consumed on a typical day was 2.2, the average use of marijuana was 1.2, and that of cocaine was 2.5. 66.8% of the participants have consumed alcohol at some time in their life, 49.9% have consumed alcohol in the last year. 18.5% have consumed cigarettes at least once in their life and only 13.6% consumed it in the last year. 7.2% of adolescents have used marijuana at some time in their life and only 3.8% used it in the last year. 3.4% have used cocaine at some time in their life and 1.9% in the last year. Conclusions: The prevalence of licit and illicit drug use shows a significant increase, which is worrying, since during adolescence any amount consumed is risky and harmful to physical and mental health. Keywords: Adolescent; Drugs; Illicit drugs, COVID-19